Energy Balance and Prostate Cancer (Energy Balance and Cancer,, 2018)
This volume provides a comprehensive treatise on the latest studies linking prostate cancer with energy balance, which together constitute a major challenge and opportunity for research scientists and clinicians especially those dealing with the expanding population of older men confronted with obesity and associated comorbidities. This volume should be a valuable resource to physicians, oncologists, urologists, endocrinologists, nurses, nutritionists, dieticians, and exercise therapists dealing with men with energy balance issues and/or questions regarding the linkage between energy balance and cancer. Moreover, this volume should serve as an important resource for cancer researchers especially for scientists studying lifestyle modification and prevention strategies to better understand and disrupt the linkage between obesity and cancer.